2006
DOI: 10.1098/rspb.2006.3632
|View full text |Cite
|
Sign up to set email alerts
|

Are algal communities driven toward maximum biomass?

Abstract: In this continental-scale study, we show that in major benthic and planktonic stream habitats, algal biovolume-a proxy measure of biomass-is a unimodal function of species richness (SR). The biovolume peak is observed at intermediate to high SR in the benthos but at low richness in the phytoplankton. The unimodal nature of the biomass-diversity relationship implies that a decline in algal biomass with potential harmful effects on all higher trophic levels, from invertebrates to fish, can result from either exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 50 publications
2
20
0
Order By: Relevance
“…2 is in the series of lakes that show particularly high planktonic biovolumes at relatively low to intermediate levels of diversity. This result is in agreement with work on stream communities by Passy & Legendre (2006), who demonstrated that biovolumes should peak at intermediate to high levels of species diversity in the benthos, but at low levels of species diversity in the plankton. They attributed this difference to the higher niche dimensionality of benthic habitats relative to comparably more homogenous planktonic zones.…”
Section: Discussionsupporting
confidence: 92%
“…2 is in the series of lakes that show particularly high planktonic biovolumes at relatively low to intermediate levels of diversity. This result is in agreement with work on stream communities by Passy & Legendre (2006), who demonstrated that biovolumes should peak at intermediate to high levels of species diversity in the benthos, but at low levels of species diversity in the plankton. They attributed this difference to the higher niche dimensionality of benthic habitats relative to comparably more homogenous planktonic zones.…”
Section: Discussionsupporting
confidence: 92%
“…Apart from turbulent water motion and circulation, which homogenize the planktonic environment, the nutrient gradients in the plankton are further disrupted by the sinking of the algae (39). These fundamental differences between benthic and planktonic habitats in terms of number and length of the resource gradients have been implicated in the profound disparity between the two communities in taxonomic and allometric organization and functioning (40)(41)(42). Therefore, lacking the complex gradient structure of the benthos, the phytoplankton was expected to respond to nutrient enrichment like a 2D community.…”
Section: Resultsmentioning
confidence: 99%
“…Diatom richness was calculated as the number of species in 300 cell counts. More information on the habitats, sampling, and laboratory techniques is given in Passy and Legendre (41). Diatom richness was regressed against NLR in the three studied habitats by using a curve-fitting program (45).…”
Section: Methodsmentioning
confidence: 99%
“…The environmental implications of this finding are far reaching because it reveals that a continuing loss of wetlands, already exceeding 52 million hectares in the conterminous United States alone (Mitsch and Gosselink 2007), may lead to algal biodiversity decline in streams with a subsequent reduction in primary productivity and biomass (Cardinale et al 2005, Passy andLegendre 2006 ). It is expected that stream ecosystem health will improve with wetland restoration that produces sufficient amounts of soil organic matter, DOC, and iron in the watershed and facilitates micronutrient fluxes into streams.…”
Section: Discussionmentioning
confidence: 99%